Fatores de risco para infecção por toxoplasma gondii e desenvolvimento da retinocoroidite toxoplásmica - Ferreira, Ana Iara da Costa (2011)
Toxoplasma gondii (T. gondii) infects humans among other ways, from the gastrointestinal tract, site of expression of ABO antigens through epistatic interactions between ABO, Secretor and Lewis genes. The toxoplasmic retinochoroiditis (TR) disease resulting from this infection is considered the main cause of posterior uveitis. Objective: To evaluate the risk factors that contribute to infection with T. gondii and development of TR. Materials and Methods: After obtaining informed consent (case 050/2009), peripheral blood and serum samples from 357 patients were analyzed. Patients were divided in two groups according to presence (n=82) or absence (n=275) of clinical diagnosis of TR. ABO and Lewis phenotyping were performed using the methods of hemagglutination in tubes and gel columns, respectively. Indirect immunofluorescence (IFI), ELISA and avidity test were used to define titration and avidity of the anti-T. gondii antibodies. The genotypes FUT2 and FUT3 were identified by PCR-RFLP and the parasite DNA by conventional PCR. Results: From the overall 357 analyzed samples, 74.8% were ELISA reagents and 25.2% were non reagent for IgG anti-T. gondii. IgM antibodies were not found and any samples. High titer (≥ 4000) were observed in 8.1% of the patients with TR and 1% of those with other ocular diseases (ODO) (p=0.03), whereas the values of high avidity (≥ 60%) were similar between the groups (p=0.44). The PCR results were positive in 21/62 (33.9%) with TR and 1/101 xviii (0.9%) among those with ODO and reagents for IgG anti-T. gondii (p<0.0001). Direct contact with cat and / or dog (p=0.009) and ingestion of raw or undercooked meat (p=0.03) were associated with infection by T. gondii but not the TR. The Le(a-b+) phenotype (p=0.03) showed a lower risk for infection, while the Le(a+b-) phenotype (p=0.08) seems to favor the development of TR. Conclusions: The results demonstrate high frequency of presumable TR among patients with ocular diseases. Besides reveal that majority of patients with TR present low titers of IgG anti-T. gondii, with high avidity and that T. gondii can be find in the peripheral blood of approximately one third of patients independent of ocular lesions resulting from toxoplasmosis. The presence of dogs and cats as well as ingestion of raw or undercooked meat increases the risk of infection by T. gondii, but does not influence the development of TR. The high Leb antigen expression reflects protective effect against infection with T. gondii, as well as the antigen Lea seems to favor the development of TR.